DETERMINAN PELAPORAN SPT - Oktafiani, Nur; Lutfillah, Novrida Qudsi (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2020)
The purpose of this research was to know the effects of aplication of e-filing, internet understanding and awareness of tax payers on SPT reporting compliance. This research uses descriptive quantitative method. The data used in this study are primary data, the primary data are from questionnaires distributed by researchers through google forms. The result of this research indicate that internet understanding has an effect on compliance reporting SPT while the apllication of e-filing and awarness of tax payers has no effect on compliance reporting SPT.